(untitled) (Research, Society and Development, 2024)
Objective: To investigate the role of intestinal dysbiosis in weight loss through an integrative review of the literature. Methodology: An integrative review was carried out following steps that included defining the research question and directories, selecting and extracting data from relevant scientific articles, and critically analyzing them. Databases such as SciELO, CAPES Periodical Portal, PubMed, and LILACS were utilized. Results: Out of 728 articles initially found from 2019 onwards, 15 were selected after applying inclusion and exclusion criteria. These studies highlighted the importance of the Firmicutes/Bacteroidetes ratio and bacterial metabolites, such as short-chain fatty acids, in the metabolic interactions that regulate weight and energy. Conclusions: The research underscores the need for future studies to expand understanding of dysbiosis and its impact on obesity, aiming for more effective and sustainable treatment strategies.